Immunomodulatory TGF-β Signaling in Hepatocellular Carcinoma. Issue 11 (November 2019) - Chen, Jian; Gingold, Julian A.; Su, Xiaoping
Abstract : Hepatocellular carcinoma (HCC) is an inflammation-induced and chemotherapy-resistant cancer. Dysregulated signaling in the transforming growth factor beta (TGF-β) pathway plays a central role in inflammation, fibrogenesis, and immunomodulation in the HCC microenvironment. This review dissects the genetic landscape of the TGF-β superfamily genes in HCC and discusses the essential effects of this pathway on the tumor immune microenvironment. We highlight the TGF-β signature as a potential biomarker for identifying individualized immunotherapeutic approaches in HCC. An improved understanding of the detailed mechanisms of liver cancer immunogenicity and the specific role of TGF-β in mediating immunotherapy resistance in HCC will provide important insights into HCC immune escape and promote the development of biomarker-derived combination immunotherapies for HCC. Highlights: Highly activated TGF-β in hepatocellular carcinoma (HCC) is significantly associated with immune cell exhaustion, while inactivated TGF-β is correlated with impaired DNA repair. The combination of TGF-β inhibitors and immune-checkpoint inhibitors successfully induced complete responses in mouse cancer models, highlighting the key immunosuppressive role of TGF-β signaling in regulating HCC immunotherapy. A novel immune-based classification identified three HCC tumor classes in the tumor microenvironment: the immune class, the intermediate immune class, and the immune exclusion class. Treatment of tumors in each class is likely to require specific immunotherapeutic approaches. Deep single-cell RNA sequencing of tumor-infiltrating lymphocytes identified molecular characteristics in the microenvironment that may guide future therapeutic strategies.